Regulators of Actin Dynamics in Gastrointestinal Tract Tumors - Konrad Steinestel; Eva Wardelmann; Wolfgang Hartmann; Inga Grünewald (Gastroenterology Research and Practice)
Reorganization of the actin cytoskeleton underlies cell migration in a wide variety of physiological and pathological processes, such as embryonic development, wound healing, and tumor cell invasion. It has been shown that actin assembly and disassembly are precisely regulated by intracellular signaling cascades that respond to changes in the cell microenvironment, ligand binding to surface receptors, or oncogenic transformation of the cell. Actin-nucleating and actin-depolymerizing (ANFs/ADFs) and nucleation-promoting factors (NPFs) regulate cytoskeletal dynamics at the leading edge of migrating cells, thereby modulating cell shape; these proteins facilitate cellular movement and mediate degradation of the surrounding extracellular matrix by secretion of lytic proteases, thus eliminating barriers for tumor cell invasion. Accordingly, expression and activity of these actin-binding proteins have been linked to enhanced metastasis and poor prognosis in a variety of malignancies. In this review, we will summarize what is known about expression patterns and the functional role of actin regulators in gastrointestinal tumors and evaluate first pharmacological approaches to prevent invasion and metastatic dissemination of malignant cells.